2002
DOI: 10.1002/1521-3757(20020118)114:2<339::aid-ange339>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Electrical Conductivity and Self-Assembly of Regioregular Polythiophene by Block Copolymerization: Nanowire Morphologies in New Di- and Triblock Copolymers

Abstract: Over two decades ago the discovery of electrical conductivity in conjugated polymers spurred a tremendous amount of effort aimed at the development of practical conducting plastics. [1] One of the primary motivations was the hope of fabricating inexpensive, lightweight conducting materials. Those efforts have been coming to fruition in recent years with the development of polymer-based light-emitting diodes, [2] field-effect transistors, [3] elements for active matrix displays, [4] and all-polymer integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
53
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 28 publications
1
53
1
Order By: Relevance
“…In contrast, the nanofibrils in the block copolymer AFM image are separated by distinct dark regions (Figure 1 b), which could indicate the location of the PEO block. These observations are consistent with previously reported data on P3HT‐containing block copolymer thin films 10. Figure 1 c shows small‐angle X‐ray scattering (SAXS) profiles obtained from bulk samples of both neat P3HT‐PEO and a P3HT‐PEO/lithium salt mixture.…”
Section: Methodssupporting
confidence: 91%
“…In contrast, the nanofibrils in the block copolymer AFM image are separated by distinct dark regions (Figure 1 b), which could indicate the location of the PEO block. These observations are consistent with previously reported data on P3HT‐containing block copolymer thin films 10. Figure 1 c shows small‐angle X‐ray scattering (SAXS) profiles obtained from bulk samples of both neat P3HT‐PEO and a P3HT‐PEO/lithium salt mixture.…”
Section: Methodssupporting
confidence: 91%
“…The orientation of the cylinders is random, and dotlike and elongated structures suggest vertically and horizontally oriented cylinders. This is in contrast to fibrillar structures commonly observed in films of P3HT and P3HT block copolymers 25. Here, the bright domains are due to aggregation of perylene bisimide.…”
Section: Methodscontrasting
confidence: 69%
“…13À17 McCullough and co-workers first showed that P3HT block copolymers form locally ordered short nanofibrils in drop-cast films. 18 In a later study, they found that reducing the bulkiness of the coil block improved the ordering in drop-cast films of P3HT block copolymers with 17 wt % P3HT. 19 Dai and co-workers have demonstrated that ordered assemblies of P3HT block copolymers can be formed through thermal annealing when P3HT block content was less than 70 wt %.…”
mentioning
confidence: 99%